A tsetse and tabanid fly survey of African great apes habitats reveals the presence of a novel trypanosome lineage but the absence of Trypanosoma brucei. Issue 12 (October 2015) - Votýpka, Jan; Rádrová, Jana; Skalický, Tomáš; Jirků, Milan; Jirsová, Dagmar; Mihalca, Andrei D.; D'Amico, Gianluca; Petrželková, Klára J.; Modrý, David; Lukeš, Julius
Graphical abstract: Highlights: The trypanosome biodiversity and feeding preferences of tsetse and tabanid flies are presented. Tsetse, but not tabanid, flies transmit a surprisingly wide spectrum of trypanosomes. Five of eight Trypanosoma spp. identified were encountered for the first time. Blood meals of ∼1000 forest tsetse flies were examined by high throughput sequencing. Tsetse flies' feeding opportunism includes buffaloes, humans, antelopes and suids. Abstract: Tsetse and tabanid flies transmit several Trypanosoma species, some of which are human and livestock pathogens of major medical and socioeconomic impact in Africa. Recent advances in molecular techniques and phylogenetic analyses have revealed a growing diversity of previously unidentified tsetse-transmitted trypanosomes potentially pathogenic to livestock and/or other domestic animals as well as wildlife, including African great apes. To map the distribution, prevalence and co-occurrence of known and novel trypanosome species, we analyzed tsetse and tabanid flies collected in the primary forested part of the Dzanga-Sangha Protected Areas, Central African Republic, which hosts a broad spectrum of wildlife including primates and is virtually devoid of domestic animals. Altogether, 564 tsetse flies and 81 tabanid flies were individually screened for the presence of trypanosomes using 18S rRNA-specific nested PCR. Herein, we demonstrate that wildlife animals are parasitized by a surprisingly wide range of trypanosome species that in some cases may circulate via these insect vectors. While one-third of the examined tsetse flies harbored trypanosomes either from the Trypanosoma theileri, Trypanosoma congolense or Trypanosoma simiae complex, or one of the three new members of the genus Trypanosoma (strains 'Bai', 'Ngbanda' and 'Didon'), more than half of the tabanid flies exclusively carried T. theileri . To establish the putative vertebrate hosts of the novel trypanosome species, we further analyzed the provenance of blood meals of tsetse flies. DNA individually isolated from 1033 specimens of Glossina spp. and subjected to high-throughput library-based screening proved that most of the examined tsetse flies engorged on wild ruminants (buffalo, sitatunga, bongo), humans and suids. Moreover, they also fed (albeit more rarely) on other vertebrates, thus providing indirect but convincing evidence that trypanosomes can be transmitted via these vectors among a wide range of warm- and cold-blooded hosts.